2016
DOI: 10.1103/physreve.93.032141
|View full text |Cite
|
Sign up to set email alerts
|

Off-equilibrium scaling behaviors driven by time-dependent external fields in three-dimensionalO(N)vector models

Abstract: We consider the dynamical off-equilibrium behavior of the three-dimensional O(N) vector model in the presence of a slowly varying time-dependent spatially uniform magnetic field H(t)=h(t)e, where e is an N-dimensional constant unit vector, h(t)=t/t(s), and t(s) is a time scale, at fixed temperature T≤T(c), where T(c) corresponds to the continuous order-disorder transition. The dynamic evolutions start from equilibrium configurations at h(i)<0, correspondingly t(i)<0, and end at time t(f)>0 with h(t(f))>0, or v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 62 publications
(112 reference statements)
10
34
0
Order By: Relevance
“…The scaling relations in eqs (4.5,4.7) apply beyond the spherical limit n → ∞ and are in agreement with the numerically obtained scaling behaviour for a 3D Heisenberg ferromagnet [75]. Indeed, in the case T < T c , we showed that the dynamics is independent on the number of…”
Section: Hysteresis In the Round-trip Protocolsupporting
confidence: 87%
See 4 more Smart Citations
“…The scaling relations in eqs (4.5,4.7) apply beyond the spherical limit n → ∞ and are in agreement with the numerically obtained scaling behaviour for a 3D Heisenberg ferromagnet [75]. Indeed, in the case T < T c , we showed that the dynamics is independent on the number of…”
Section: Hysteresis In the Round-trip Protocolsupporting
confidence: 87%
“…As mentioned, all results presented in this work are derived in the large-n limit. However, we argued that the dynamics of the system is not affected by the number of transverse components so that our results apply for any finite n ≥ 2, as confirmed by a comparison with numerical studies [75].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations